The burden of gastric cancer attributed to high salt intake and predictions through the year 2042: a cross-national comparative analysis of China, Japan, and South Korea - Liu, Wei; Peng, Zhen-zhen; Zhao, Dong-qin; Liu, Yang; Liao, Kui (Frontiers in Nutrition, 2025)
BackgroundGastric cancer remains a significant health burden, particularly in East Asia, where high salt intake is a major risk factor. This study assesses the gastric cancer burden attributable to high salt intake in China, Japan, and South Korea.MethodsWe analyzed data from the GBD 2021 database, including age-standardized mortality rates (ASMR), age-standardized DALY rates (ASDR), and population attributable fraction (PAF) related to high salt intake. The study focused on individuals aged 25 and above, covering global, Chinese, Japanese, and South Korean populations, with trends from 1990 to 2021 and projections through 2042.ResultsFrom 1990 to 2021, the gastric cancer burden attributable to high salt intake significantly decreased globally and in China, Japan, and South Korea. Globally, ASMR decreased from 1.74 per 100,000 in 1990 to 0.89 per 100,000 in 2021 (EAPC = −2.26). In China, ASMR decreased from 3.85 per 100,000 in 1990 to 1.78 per 100,000 in 2021 (EAPC = −2.56), with similar declines in Japan and South Korea. Gender disparities remain, with men bearing a significantly higher gastric cancer burden, especially among the elderly.ConclusionWhile high salt intake’s contribution to gastric cancer decreased from 1990 to 2021, it remains a major factor in mortality and DALYs, particularly among elderly and male populations. However, these findings should be interpreted with caution due to reliance on modeled population-level data and the inability to establish causality from observational sources.